The behaviour of the equity yield and its relation with the bond yield: The role of inflation - David G. McMillan (International Journal of Financial Studies, 2018)
Understanding the behaviour of the equity yield and its relation to the bond yield is important for portfolio managers and those engaged in modelling the interaction between asset classes. During the mid-1900s, the equity yield-which was previously greater than the bond yield-declined, while the bond yield rose and became higher. Research, seeking to understand this, put forward the view that stock and bond return volatility is key. Evidence from the 2000s suggest that the relative values of the equity and bond yield have flipped again, with the former now greater. Empirical evidence presented here shows that during such periods, the hypothesised relation between the equity yield and the bond yield and the two volatilities also changes, with the signs reversed. Moreover, there is noticeable variation in the coefficient values. This paper argues that the relative equity and bond yield values are, to a large extent, driven by inflation volatility. High inflation volatility persisted during the first half of the twentieth century when the equity yield was higher. This was followed by more benign inflation volatility when the bond yield became higher. Evidence for a long span of US data, and shorter German, Japanese, and UK data, suggests the recent rise in the equity yield is accompanied by an uptick in inflation volatility relative to its recent tranquillity.
Keywords: C22; G12; 330; equity yield; bond yield; volatility; time-variation; inflation